Three key drivers in devising a responsive curriculum in South African higher education institutions - Human-Hendricks, N.; Meier, C. (South African Journal of Higher Education, 2024)
South African higher education institutions are constantly required to respond to a series of tensions and challenges within higher education curriculum reform. This implies the need for urgent attention to a truly responsive curriculum in South African higher education. This article reports on research involving a critical interpretative literature analysis. Three drivers are identified in devising a responsive curriculum in South African higher education, namely the need for decolonisation, accommodation of disruptive technologies, and features of graduateness in the 21st century. The discussion of each of these drivers is preceded by a brief conceptualisation of the notion of a responsive curriculum. The research conclusion indicates that it should be a strategic priority of each higher education institution in South Africa to acknowledge the three curriculum design drivers as mentioned above, and accordingly upskill and empower academics in the quest for conceptualising and developing a constructively aligned curriculum that is responsive to the ever-changing societal and global needs.